PREPARATION OF ACTIVATED CARBON FROM SILK COTTON WOOD AND COCONUT SHELL BY PYROLISIS WITH CERAMIC FURNACE - Winarto Haryadi; Muchalal Muchalal; Robby Noor Cahyono (Universitas Gadjah Mada, 2005)
Preparation of activated carbon from silk cotton wood and coconut shell has been done. Carbon was made by pyrolysis process in the Muchalal furnace with 3000 watt electric power. The electric power was increased gradually from 1000, 2000 and then 3000 watt with interval 2 hours during 7 hours. Carbon was activated in Muchalal furnace with 4000 watt electric power during 2 hours and flowed with nitrogen gas. Product of the activated carbon was compared to standart product with several analysis including the surface area, acetic acid adsorption, iod adsorption and vapour adsorption. The results of analysis showed that surface area for silk cotton wood carbon, coconut shell carbon, and E.Merck product were 288.8072 m2/g, 222.9387 m2/g and 610.5543 m2/g, respectively. Acetic acid adsorption for silk cotton wood carbon, coconut shell carbon, and standart product were 157.391 mg/g, 132.791 mg/g, and 186.911 mg/g, respectively. Iodine adsorption for cotton wood carbon, coconut shell carbon, and standart product were 251.685 mg/g, 207.270 mg/g and 310.905 mg/g, respectively. Vapour adsorption for cotton wood carbon, coconut shell carbon and standart product were 12%, 4%,and 14%., respectively.